The famous five : five on a treasure Island - Blyton, Enid. (b, 2015)
The intrepid five are determined to ferret out the thief who is victimizing Kirrin Cottage, but with no proof, they are stumped. Then they discover a map, and a secret hideaway. All of a sudden, things begin to fall into place
Keywords: Action and adventure fiction